Stereotactic body radiotherapy based treatment for hepatocellular carcinoma with extensive portal vein tumor thrombosis - Shui, Yongjie (Radiat Oncol, 2018)
BACKGROUND: There is currently no worldwide consensus for the management of hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). We evaluated the efficacy of stereotactic body radiotherapy (SBRT) as the initial treatment for HCC with extensive PVTT based on a relatively large number of patients. METHODS: In our multidisciplinary approach for patients with hepatobiliary tumors, SBRT is recommended for unresectable HCC with PVTT or those with contraindication for transarterial chemoembolization (TACE). The aim is to shrink the tumor thrombus and preserve adequate portal venous flow, thus facilitating subsequent treatments such as TACE and tumor resection. In the present study, 70 continuous cases of HCC patients with extensive PVTT initially treated with SBRT were studied. The median follow-up period was 9.5 months (range, 1.0–21.0 months). The dynamic changes of tumor thrombosis with time after SBRT were also analyzed. RESULTS: The median survival time for the whole group was 10.0 months (95% CI, 7.7–12.3 months), with a 6- and 12-month overall survival (OS) rate of 67.3%, and 40.0% respectively. Patients who received combined SBRT and TACE showed significantly longer OS than those without indication for TACE after SBRT (12.0 ± 1.6 vs. 3.0 ± 1.0 months). Patients with good response to radiation usually had better survival. SBRT was well tolerated in our patient series. CONCLUSIONS: In conclusion, SBRT used as the initial treatment for HCC patients with extensive PVTT originally unsuitable for resection or TACE can achieve adequate thrombus shrinkage and portal vein flow restoration in the majority of cases. It could thus offer the patients an opportunity to undergo further treatment such as resection or TACE procedure. Such therapeutic strategy may result in survival advantage, especially for those who do receive combined modality with SBRT.